Implementasi Lesson Study dan Pendekatan Student Centered Learning dalam Pembelajaran Fonologi - Adawiyah, Aprilla; Ningsih, D. Nurfajrin (Universitas Suryakancana, 2023)
This article will describe improving the quality of learning in Phonology courses with lesson study and student centered learning approaches. The study used the Lewis model lesson study method. Learning is carried out using the flipped classroom model (online and offline). In online classes, students access the Schoology application and actively participate in discussions. Meanwhile, in offline classes, students review online class material with an emphasis on practice or exercises. The results showed that there was an increase in learning from cycle to cycle. The number of students actively participating in learning in online and offline classes is also getting better. Lectures are not boring and students are enthusiastic in learning. The results of the questionnaire showed that 86.2% liked flip classroom learning or online and offline classes.Keywords: flipped; phonology; lesson study; student centeredABSTRAKArtikel ini akan mendeskripsikan peningkatan kualitas pembelajaran pada mata kuliah Fonologi dengan lesson study dan pendekatan student centered learning. Penelitian menggunakan metode lesson study model Lewis. Pembelajaran dilaksanakan dengan model flipped classroom (daring dan luring). Di kelas daring, mahasiswa mengakses aplikasi Schoology dan berpartisipasi aktif dalam diskusi. Sementara itu, pada kelas luring, mahasiswa merevieu materiÂ kelas online dengan penekankan pada praktik atau latihan. Hasil penelitian menunjukkan, terdapat peningkatan pembelajaran dari siklus ke siklus. Jumlah mahasiswa yang berpartisipasi aktif dalam pembelajaran di kelas daring maupun luring juga makin membaik. Perkuliahan menjadi tidak membosankan dan mahasiswa antusias dalam belajar. Hasil angket menunjukkan sebanyak 86,2% menyukai pembelajaran flip classroom atau kelas online dan offline.Kata Kunci: flipped; fonologi; lesson study; student centeredÂ